Loď nemůže plout bez kormidelníka (A ship cannot float without a helmsman) (ENTHYMEMA, 2025)
Obituary of Professor Peter Steiner.
Keywords: Peter Steiner; Czech Structuralism; Russian Formalism; Marxism; Herbartianism; Semiotics; Political-historical Contextual Research